2017
DOI: 10.1590/s1677-5538.ibju.2016.0177
|View full text |Cite
|
Sign up to set email alerts
|

Effect of platelet-rich plasma on polypropylene meshes implanted in the rabbit vagina: histological analysis

Abstract: Purpose The polypropylene mesh (PPM) is used in many surgical interventions because of its good incorporation and accessibility. However, potential mesh-related complications are common. Platelet-rich plasma (PRP) improves the healing of wounds and is inexpensive. Thus, the purpose of this study was to analyze the effect of the PRP-gel coating of a PPM on inflammation, production of collagen, and smooth muscle in the rabbit vagina.Materials and Methods The intervention consisted of a 1.5cm incision and divulsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…It has been used in atrophic diseases such as vaginal lichen sclerosis, stress urinary incontinence, episiotomy scars, and lubrication disorders (2,19) . PRP has been found to be effective in mesh erosion; PRP-coated mesh treatment has been revealed by in vitro and animal studies to result in better wound healing, increased synthesis of collagen 3, and neovascularization (20,21) .…”
Section: Discussionmentioning
confidence: 99%
“…It has been used in atrophic diseases such as vaginal lichen sclerosis, stress urinary incontinence, episiotomy scars, and lubrication disorders (2,19) . PRP has been found to be effective in mesh erosion; PRP-coated mesh treatment has been revealed by in vitro and animal studies to result in better wound healing, increased synthesis of collagen 3, and neovascularization (20,21) .…”
Section: Discussionmentioning
confidence: 99%
“…Vaginal exposure was observed in both the groups. In the animals without exposures, there were no differences in the inflammatory infiltrate apart from more immature collagen [48]. The above experiments have partially conflicting results, and neither were they designed to explore mechanisms behind these differences.…”
Section: Synthetic Durable Textile Materialsmentioning
confidence: 98%
“…More specifically, Parizzi et al reported a decreased inflammatory infiltration at 30 days and increased collagen III concentration at 90 days in the histologic specimen of PRP-coated meshes which were implanted in the vaginal mucosa of 15 rabbits. 28 On the contrary, Belebecha et al found reduced levels of myeloperoxidase and N-acetylglucosamide activities as well as decreased oxidative stress and elevated antioxidant levels without difference in inflammatory cells in the specimen of rabbits with PRP-coated polypropylene mesh compared to those with uncoated polypropylene mesh. 29 Finally, an in vitro study by Medel et al demonstrated the beneficial effect of PRP in enhancing the cell attachment to the surface of both Vicryl and Restorelle meshes compared to no PRP-coated meshes as proved by light microscopic evaluation (9875 ± 996 vs 1006 ± 84 cells/cm 2 , 9.8 times increase and 3724 ± 407 vs 649 ± 53 cells/cm 2 , 5.7 times increase, respectively).…”
Section: Resultsmentioning
confidence: 96%